Application of Hydrocyclone and UV Radiation as a Ballast Water Treatment Method - Kurtela, Željko; Komadina, Pavao (Promet - Traffic&Transportation, 2010)
The ballast water exchange methods in open sea are, for the time being, the prevailing procedures accepted by shipowners. However, such methods do not guarantee full efficacy in elimination of allochthonous organisms. Besides, in some navigation zones, in particular in the closed seas, not even the criteria prescribed by international regulations can be fulfilled, i.e. the position of a ship exchanging ballast must be farther than 200Nm from the shore (alternatively 50Nm) at the sea depth exceeding 200m. Numerous research attempts on various treatment methods lead to the conclusion that there is still no scientific opinion on the final choice of methods for wide application on board. The treatment methods, such as hydrocyclone separation in the first stage and UV radiation in the second stage, stand a good chance for application on board. Advantages of such a combined method are in the very application of treatment that can be performed during all stages of ballast water treatment, i.e. loading ballast, voyage in ballast and discharging ballast. In closed seas and on shorter routes the operational advantages of hydrocyclone and UV radiation could be the prevailing factor for application. Within the research on the possible application of ballast water treatment by hydrocyclone and UV radiation, a pilot plant with hydrocyclone cluster and UV device was constructed. The research carried out on the pilot plant installed on board the m/v ‘’Naše more’’ proved the effectiveness of such ballast water treatment method and offered a new approach in using hydrocyclone for the inactivation of organisms by hydrodynamic forces. This approach has largely increased the efficacy of the device and a new method for utilization of hydrocyclone in ballast water treatment on board has been discovered. KEY WORDS: ballast water treatment, hydrocyclone, UV radiation, application of method, pilot plant, hydrodynamic forces